The Role Of Development In Increasing The Working Achievement Of Education And Culture Department Employees Muara Enim District - Etyindriani Etyindriani; Yusawati Yusawati; Nindiyawati Nindiyawati (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The author conducted research with the aim of knowing and analyzing how the role of coaching in improving employee performance performance of employees of the Muara Enim Regency Education and Culture Office. Discipline training for employees of the Muara Enim District Education and Culture Office in working such as time attendance and going home from work according to schedule has often been carried out. Guidance on the personality development of employees is rarely carried out, in which case there are still employees with personalities who are not good. Coaching in managing employee conflict and competition has been carried out on an ongoing basis, but there are still employees who are unable to solve problems at work even though problems with co-workers often occur. Employees at work with mutual respect and employees have tolerance towards colleagues and employees have the awareness that mutual respect is very important to apply. Every employee has the opportunity for promotion and self-development. Employees have the opportunity to develop their potential, talent, attitude, behavior and personality through learning and experience.